New insight into the kinetic study on the different loadings of the CuO/CNT catalyst and its optimization for p-chloroaniline photodegradation. Issue 13 (1st June 2022) - Farahain binti Khusnun, Nur; Jalil, Aishah Abdul; Ahmad, Arshad; Ikram, Muhammad; Hassan, Nurul Sahida; Nabgan, Walid; Bahari, Mahadi; Kasmani, Rafiziana; Norazahar, Norafneeza
Abstract : The effect of the copper (Cu) content on Cu oxide loaded onto a carbon nanotube (CuO/CNT) catalyst on the mechanistic, kinetic, and photonic efficiency of the photodegradation of p -chloroaniline (PCA) under visible (Vis) and ultraviolet (UV) light irradiation has been explored. Abstract : The effect of the copper (Cu) content on Cu oxide loaded onto a carbon nanotube (CuO/CNT) catalyst on the mechanistic, kinetic, and photonic efficiency of the photodegradation of p -chloroaniline (PCA) under visible (Vis) and ultraviolet (UV) light irradiation has been explored. For low-loading (1–5 wt%) CuO/CNTs, photodegradation performed better under UV (>84%) rather than the Vis system; this may be due to the presence of abundant defect sites on both CuO and CNTs, which allowed the multielectron reduction of oxygen at their impurity levels to generate more hydrogen peroxide and subsequent ·OH radicals. The active species under UV were in the following order: h + ≫ e − > ·OH, while it was vice versa for the Vis system with a well-balanced 50 wt% CuO/CNT catalyst that exhibited a similar performance. The kinetic study showed the transition of the kinetic order from the zeroth to the first order on increasing the PCA concentration under the Vis system and vice versa for the UV system. The Thiele modulus ( ϕ ) further confirmed that the effect of internal mass transfer was negligible under UV light. In contrast, the transition from mass transfer to kinetic control limitation was observed under the Vis system. The optimum PCA degradation predicted from the response surface analysis was 97.36% at the reaction pH of 7.3, catalyst dosage of 0.45 g L −1, and initial PCA concentration of 11.02 mg L −1 . The condition obtained was fairly close to the forecasted value with an error of 0.26%.